World Investment Report 2011 - United Nations Conference on Trade; Development (United Nations, 2011)
This report is widely regarded as the most authoritative source of data and analysis on the activities of transnational corporations, national and international regulatory regimes, and their implications for development. The 2011 edition focuses on the strategic use of non-equity modalities (e.g. contract manufacturing, service outsourcing, licensing, franchising, etc.) by transnational corporations in their management of global value chains and international operations. Additional highlights include a discussion of the interplay between foreign direct investment and industrial policy, as well as an assessment of the origin, rise and global map of state-owned transnational corporations. It also contains a statistical annex with data on flows and stocks of foreign direct investment for 196 economies.